Digital national waiting time information system - View of Finnish public oral healthcare managers - Söderlund, Riitta (Elsevier, 2025)
Objectives
The study evaluated the digital national waiting time information system from the point of view of oral healthcare managers in Finland in 2021. The information system (IS) was implemented in 2014, primarily to monitor waiting times in public healthcare. The system reported the information on realised waiting times on the Internet.
Methods
We gathered the data using a cross-sectional survey. Evaluating the system was based on a modified IS success model with the dimensions of information quality, system quality, individual impact and organisational impact. We used convenience sampling when including in the study managers working in public primary oral healthcare in the spring of 2021.
Results
The managers (n = 97) perceived it as easy to access the waiting time information on one website, but they evaluated the information as low quality. The information on realised waiting times supported them in the management of current waiting times to a minor degree. The managers associated the information inaccuracy in the national system with dental nurses’ poor data entry in electronic patient ISs in oral healthcare organisations. The inaccuracy meant that waiting time monitoring data was not valid.
Conclusions
Our modified IS success model was sufficient to ascertain that poor information quality likely influenced the effectiveness of managers in information-driven waiting time management. Information must be relevant and accurate to promote the success of ISs. Further research is required to explore how to improve the design of national ISs from the point of view of different stakeholders in healthcare.